Punishment for sale: private prisons, big business and the incarceration binge - Selman, Donna (Issues in crime & justice, 2010)
America's incarceration binge : the expansion of prisons, budgets and injustice -- The big government "problem" and the Kentucky fried prison "solution" -- The prison-industrial complex : profits, vested interests and politics -- Confronting problems : blame prisoners and contracts then get a bailout -- A critical look at the efficiency and overhead costs of private prisons -- Conclusion : back to the future